Kajian kecenderungan pneumonia pada balita di Kota Bitung tahun 2015-2017 - Waani, J.; Ottay, Ronald I.; Palandeng, Henry M. F. (UNIVERSITAS SAM RATULANGI, 2018)
Background: According to the World Health Organization (WHO), in 2016 the main causes of deaths of children under five years are pneumonia (14%), diarrhea (14%), other infections (9%), malaria (8%), and noncomunicable diseases ( 4%), hence WHO states that pneumonia is the leading killer of children worldwide and is also called the forgotten killer of children. The incidence of pneumonia has decreased but it is still the highest cause of children under-five years’ mortality.Aim: This study aims to determine the description and trends of pneumonia in infants in the city of Bitung in 2015-2017.Method: This study is a descriptive study using a cross-sectional research design. And using secondary data taken from the health profile book of the City of Bitung in 2015-2017.Results: The results of the study found that pneumonia cases in children under five years in 2015 added up to 58 cases from the target of 1863 cases, for 2016 the number of cases found was 56 cases from the target of 2057 cases, and for 2017 the number of case findings was 50 cases with targets the findings of 2044 pneumonia cases in infants with the coverage of children with pneumonia treated only reached 3.1%, 2.7% and 2.5%.Conclusion: The number of findings and coverage of finding pneumonia in children under five years in Bitung City in 2015-2017 has decreased, and this is still very low, even far from the set target.